Modelo Prolab: ParkeaYA!: La aplicación móvil para reservar un estacionamiento y mantener tu auto seguro - Córdova Heredia, María Angélica (2024)
Currently, drivers in Lima Metropolitana face various concerns during their commutes. One of the main issues is finding a safe place to park their vehicles to avoid the risk of theft. This relevant social problem (RSP) is the focus of this thesis, which aims to present a sustainable project to address this issue, positively impacting various stakeholders, including drivers, independent parking lots, and society. The research introduces the business project named "ParkeaYa!", a mobile app that allows drivers to view available parking lots in their destination area, check space availability in the selected lot, and make a reservation with online payment. After conducting the analysis, it was determined that the proposed solution is feasible, representing an investment of S/ 315,185 and generating a Net Present Value (NPV) of S/ 2,464,179 in the first five years. Initially, the project will cover four districts (San Isidro, Miraflores, Santiago de Surco, and San Borja) due to their high demand, with eight districts being reached after the first five years and the possibility of expansion to other districts of Lima and major cities in Peru. Finally, it is highlighted that the project impacts five Sustainable Development Goals (SDGs), with a Social Profitability Index of 62% and a Social Net Present Value (VANS) of S/ 7,289,286, emphasizing its benefits in terms of security, time savings, and environmental care.